Mechanical and Microstructural Characterization of AA6061- AA7075 Dissimilar Friction Stir Welding - L. H., Shah; N. F., Zainal Ariffin; M., Ishak; A. R., Razali (2015)
In this paper, mechanical and microstructural characterizations on dissimilar friction stir welding joints of aluminium alloy AA6061 and AA7075 were conducted. Mechanical property analysis of specimens was conducted using tensile test and Vickers hardness test. Meanwhile, microstructure characterization of the optimum sample was conducted using optical microscope, scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). Results show that samples exhibit good quality appearance with minor surface defects. Fractured tensile specimens revealed that the failure occurs at the weaker aluminium side (AA6061). The highest tensile strength of 219.6 MPa was achieved using 1000 rpm rotational speed, 110 mm/min travel speed and 3˚ tilt angle. The results from the micro-hardness analysis show that the highest value of 151 HV was obtained from the thermo-mechanically affected zone (TMAZ) of AA7075 matrix. Microstructure analysis on the other hand shows a single vortex lamellar structure in the weld zone, indicating good material mixing. The fracture surface of the samples indicates ductile fracture behaviour initiating from the AA6061 matrix.